2018
DOI: 10.1016/j.jpor.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Trueness and precision of digital impressions obtained using an intraoral scanner with different head size in the partially edentulous mandible

Abstract: Digital impressions are partially comparable to conventional impressions in terms of accuracy; the use of a larger scanning head may improve the accuracy for removable partial denture fabrication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 29 publications
2
96
1
3
Order By: Relevance
“…However, the total deviations for the Trios 3 Pod and the Primescan in this clinical study were higher compared with the laboratory data reported by Ender et al [9] and Iturrate et al [33]. This could be due to different evaluation methods (percentiles) and furthermore explained by the in vivo conditions and the presence of saliva, oral structures, and patient movement(s) that may influence accuracy [34][35][36].…”
Section: Discussioncontrasting
confidence: 68%
“…However, the total deviations for the Trios 3 Pod and the Primescan in this clinical study were higher compared with the laboratory data reported by Ender et al [9] and Iturrate et al [33]. This could be due to different evaluation methods (percentiles) and furthermore explained by the in vivo conditions and the presence of saliva, oral structures, and patient movement(s) that may influence accuracy [34][35][36].…”
Section: Discussioncontrasting
confidence: 68%
“…[19] ere have been significant developments in intraoral scanner technology and its design that they overcame many limitations since then [25]. ere have been numerous studies since 2015 on the accuracy of intraoral scanner images in various prosthetic and orthodontic conditions [11,[26][27][28][29][30][31]. However, most of them were with dry models.…”
Section: D Superimposition Analysis (Geomagic Verify ™ ) Showsmentioning
confidence: 99%
“…The direct technique is considered more accurate, in terms of trueness and precision (ISO), 39 to produce prosthetic products through the digital work-flow. The digital workflow allows the use of industrially precured fiberreinforced composite resins with superior mechanical properties.…”
Section: Resultsmentioning
confidence: 99%